Acoustic Territoires: Sound Culture and Everyday Life - Labelle, Brandon (New York Bloomsbury, 2010)
Acoustic Territories: Sound Culture and Everyday Life offers an expansive reading of auditory life. It provides a careful consideration of the performative dynamics inherent to sound culture and acts of listening, and discusses how auditory studies may illuminate understandings of contemporary society. Combining research on urbanism, popular culture and auditory issues, Acoustic Territories opens up multiple perspectives - it challenges debates surrounding noise pollution and charts an "acoustic politics of space" by unfolding auditory experience as located within larger cultural histories and related ideologies.Brandon LaBelle traces auditory life through a topographic structure: beginning with underground territories, through to the home as a site, and then further, to streets and neighborhoods, and finally to the sky itself. This structure follows sound as it appears in specific auditory designs, as it is mobilized within various cultural projects, and queries how it comes to circulate through everyday life as a medium for social transformation. Acoustic Territories uncovers the embedded tensions and potentiality inherent to sound as it exists in the everyday spaces around us.